Human sex-determination and disorders of sex-development (DSD). (September 2015) - Bashamboo, Anu; McElreavey, Ken
Abstract: Several new genes and pathways have been identified in recent years associated with human errors of sex-determination or DSD. SOX family gene mutations, as well as mutations involving GATA4, FOG2 and genes involved in MAP kinase signaling have been associated with virilization in 46, XX individuals or with 46, XY gonadal dysgenesis. Furthermore, mutations involving another key gene in sex-determination, NR5A1, are now known to be an important cause spermatogenic failure in the male and ovarian insufficiency in the female. These new findings offer insights into human sex-determination and highlight important differences between the human and mouse model. This review will critically examine the evidence linking gene mutations, especially MAP3K1, to non-syndromic forms of human 46, XY gonadal dysgenesis or XX testicular/ovotesticular.